Interval-valued spherical fuzzy extension of SWARA for prioritizing strategies to unlock Africa's potential in the carbon credit market - Tafuteni Chusi; Su Qian; Seyyed Edalatpanah; Yanjun Qiu; Mouhamed Bayane Bouraima; Akpa Ajayi (Computational Algorithms and Numerical Dimensions)
With growing global emphasis on climate change, carbon credits have gained traction to curb greenhouse gas emissions. Endowed with vast natural resources and potential for sustainable development, Africa is uniquely positioned to benefit from this emerging market. This article investigates how Africa can optimize its involvement in carbon credit trading to transform environmental efforts into economic benefits. By applying the Stepwise Weight Assessment Ratio Analysis (SWARA) method in an Interval-Valued Spherical Fuzzy (IVSF) setting, the study aids in collective decision-making. It highlights three critical strategies for maximizing Africa's carbon credit market potential: harnessing natural resources for carbon sequestration, creating effective legal and regulatory frameworks, and enhancing capacity building and knowledge sharing. The research offers actionable recommendations for governments leveraging these opportunities and advancing in the carbon credit market.